THE EFFECTIVENESS OF E-LEARNING IN “IDIOM BASED LEXICAL STUDIES” AT STKIP PGRI TULUNGAGUNG - Dina Kartikawati; Ika Rakhmawati (STKIP PGRI Trenggalek, 2018)
Vocabulary is one of the language elements that is important to be taught. First, Vocabulary is foundation of learning language. In learning language students must master the vocabulary to know the meaning of the new words. Without knowing the meaning of the words, it is impossible for them to understand the language. The research problems are formulated as follow, Do the students achieve better vocabulary in idiom after being taught using google classroom? The design of this research is quantitative research, which is concerned with hypothesis, formulation, testing and analysis of the relationship between two variables; dependent variable and independent variable. Both of variables are selected and observed. They are indicated into the number of data. Ary (2002: 22) states that quantitative research uses objective measurement and statistical analysis of numeric data to understand and explain phenomena. Based on the statistical calculation using SPSS 16.0, the researcher gave interpretation to significant value. Because significant value 0.000 was smaller than significant level 0.05, it can be concluded that alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. It means that there was significant effect after using google classroom to teach Idiom Based Lexical Studies. Thus, it can be concluded that by using google classroom in teaching idiom based lexical studies at the second semester at STKIP PGRI Tulungagung in the academic year of 2017/2018 is effective. So, the researcher concludes that teaching idiom based lexical studies by using google classroom is more effective and interesting for the second semester students at STKIP PGRI Tulungagung in the academic year 2017/2018. By using google classroom, students hopefully can increase their vocabulary mastery. Teachers should give motivation to students so that they will be more interested in learning activity